A New Viewpoint and Outlook on Aryl Mercaptans as Strong Nucleophiles with Various Chain Length Linked to DNA/RNA and Cadmium Oxide (CdO) Nanoparticles Sandwiched Complex - Heidari, Alireza (Asian Journal of Engineering and Applied Technology, 2021)
CdO nanoparticles show a strong peak of Plasmon absorption in ultraviolet–visible zone. A strong interaction exists between the surface of CdO nanoparticles and aryl mercaptan compounds. Aryl mercaptan compounds cause to aggregation of CdO nanoparticles linked to DNA/RNA and hence, lead to widening of peak Plasmon of CdO nanoparticles surface at 550 (nm) and emerging a new peak at higher wavelength. In the current project, this optical characteristic of CdO nanoparticles is used to time investigate of interaction between different aryl mercaptanes and CdO nanoparticles. The results were shown that aryl mercaptan compounds with shorter chain length interact faster with CdO nanoparticles. Therefore, a simple and fast method for identification of aryl mercaptanes with various chain length using red shift in surficial Plasmon absorption is presented.